2013
DOI: 10.1063/1.4829066
|View full text |Cite
|
Sign up to set email alerts
|

The interface inter-diffusion induced enhancement of the charge-trapping capability in HfO2/Al2O3 multilayered memory devices

Abstract: Nonvolatile memory devices with AlOx embedded Zr-doped HfO2 high-k gate dielectric stack J. Vac. Sci. Technol. B 32, 03D116 (2014); 10.1116/1.4867170The effect of thermal treatment induced inter-diffusion at the interfaces on the charge trapping performance of HfO2/Al2O3 nanolaminate-based memory devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…which show wonderful charge storage and retention properties as compared with those memory devices with single charge-trapping layer. [25][26][27][28][29][30] Some definite experimental evidences identified that the charge-trapping behaviors in these multilayered memory devices should be ascribed to the inter-diffusion at the interface of different high-k oxides. [25][26][27][28] Recently, some high-k composite oxides have been employed as the charge-trapping dielectrics to achieve the higher density of trapped charges in CTM devices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…which show wonderful charge storage and retention properties as compared with those memory devices with single charge-trapping layer. [25][26][27][28][29][30] Some definite experimental evidences identified that the charge-trapping behaviors in these multilayered memory devices should be ascribed to the inter-diffusion at the interface of different high-k oxides. [25][26][27][28] Recently, some high-k composite oxides have been employed as the charge-trapping dielectrics to achieve the higher density of trapped charges in CTM devices.…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30] Some definite experimental evidences identified that the charge-trapping behaviors in these multilayered memory devices should be ascribed to the inter-diffusion at the interface of different high-k oxides. [25][26][27][28] Recently, some high-k composite oxides have been employed as the charge-trapping dielectrics to achieve the higher density of trapped charges in CTM devices. [31][32][33] It was reported that the memory structure with a charge-trapping layer of (Al 2 O 3 ) 0.5 (Cu 2 O) 0.5 shows a large memory window and a high density of the trapped charges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It was also reported that the multilayered high-k charge-trapping layer, such as HfO 2 /Al 2 O 3 /HfO 2 and ZrO 2 /Al 2 O 3 /ZrO 2 etc., causes an enhancement of the charge-storage efficiency of the CTM devices. [22][23][24][25][26] In our previous study, a remarkable charge-trapping efficiency and a fast programming/erasing(P/E) speed were obtained in a CTM device with a TiAlO high-k composite chargetrapping dielectric, achieving a density of trapped charges of 9.3×10 20 …”
Section: -14mentioning
confidence: 99%
“…1,[15][16][17][18][19] Thus, the interface HfO 2 /Al 2 O 3 , which plays an important role in charge trapping behavior, is likely to appear in different parts of CTM stacked structures. And the Hf-based high-k dielectrics and its interface have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%